The relationship between principal inclusive leadership, teacher efficacy and teachers’ innovative behavior - Dongxiao, Mo; Abdul Kadir, Suhaida; Hassan, Roshafiza; Kang Mohd Sufian Kang, Enio (International Journal of Evaluation and Research in Education (IJERE), 2024)
The objective of this study was to explore the relationship among principals’ inclusive leadership, teachers’ sense of efficacy, and teachers’ innovative behaviors. A sample of 671 middle school teachers from Guangxi, China was utilized. The study revealed that the practice of inclusive leadership by principals had a positive effect on teacher efficacy. Furthermore, teacher efficacy appeared to have a beneficial effect on teacher innovative behavior. Additionally, the study showed that principal inclusive leadership significantly influenced teacher innovative behavior. Lastly, it proved that teacher efficacy played a mediating role in the relationship between principal inclusive leadership and teacher innovative behavior. The study offers strategies for enhancing teacher’s propensity for innovative conduct. When designing programs to promote teacher innovative behavior, it is important to take into account the impact of inclusive leadership by principals and the magnitude of teacher efficacy.